UNDERSTANDING GEN Z’S PURCHASE DECISION: THE ROLE OF CONSUMER CONFUSION AND INFORMATION OVERLOAD - Stiadi, Muhamad; Sukmawati, Sukmawati; Rifqi, Andi (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
This research is intended to examine how consumer confusion and information overload affect purchasing decisions among Generation Z. The findings indicate that consumer confusion does not significantly impact purchasing decisions, whereas information overload demonstrates a significant effect. The study adopts a quantitative approach involving three variables: consumer confusion and information overload as independent variables and purchasing decisions as the dependent variable. Primary data were collected through questionnaires distributed to 184 Generation Z respondents. The data analysis process included validity and reliability testing, classical assumption testing, as well as statistical analyses such as correlation, coefficient of determination, regression, and hypothesis testing. The results reveal that, partially, consumer confusion does not significantly influence purchasing decisions, reflected by a Beta value of 1%. In contrast, information overload shows a strong and significant effect with a Beta value of 82.5%. Simultaneously, both variables significantly influence purchasing decisions, as indicated by an R² value of 67.2%. These findings suggest that companies should consider both factors when aiming to enhance consumer purchasing decisions.